2022
DOI: 10.31849/reila.v4i3.11005
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Assessment Practices of EFL Lecturers with Current Curriculum Implementation: Where Policy Meets Practice

Abstract: Within the context of Indonesian higher education, the assessment focuses on the three domains of students’ competencies, namely knowledge, skills, and attitude. Therefore, this study aims to explore the assessment practice of EFL lecturers, especially the methods used in assessing the three students’ competencies. It also explores the general assessment practice and examines differences by educational degree and length of teaching experience. This quantitative study relies on survey data from 71 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding is in line with the findings by Mulyani et al, (2023) in that lecturers in their study admitted their use of various types of assessment. Similarly, the study conducted by Alfian et al, (2022) also revealed EFL lecturers' use of various assessment types to assess three domains of learning, which include language tests, observation, and performance assessment. In addition, the participants of this study are also cognizant of the diverse objectives associated with assessing students' listening skills.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is in line with the findings by Mulyani et al, (2023) in that lecturers in their study admitted their use of various types of assessment. Similarly, the study conducted by Alfian et al, (2022) also revealed EFL lecturers' use of various assessment types to assess three domains of learning, which include language tests, observation, and performance assessment. In addition, the participants of this study are also cognizant of the diverse objectives associated with assessing students' listening skills.…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, assessment, teaching, and curriculum are closely related to support student learning. Assessment is a crucial part of the curriculum because it gives information and proof of learning (Alfian et al, 2022). Tunaz (2023) indicates a close connection between instructional methods and assessment procedures.…”
Section: Introductionmentioning
confidence: 99%